CD4 Inhibits Helper T Cell Activation at Lower Affinity Threshold for Full-Length T Cell Receptors Than Single Chain Signaling Constructs - Johnson, Deborah K.; Magoffin, Wyatt; Myers, Sheldon J.; Finnell, Jordan G.; Hancock, John C.; Orton, Taylor S.; Persaud, Stephen P.; Christensen, Kenneth A.; Weber, K. Scott (Frontiers in Immunology, 2021)
CD4+ T cells are crucial for effective repression and elimination of cancer cells. Despite a paucity of CD4+ T cell receptor (TCR) clinical studies, CD4+ T cells are primed to become important therapeutics as they help circumvent tumor antigen escape and guide multifactorial immune responses. However, because CD8+ T cells directly kill tumor cells, most research has focused on the attributes of CD8+ TCRs. Less is known about how TCR affinity and CD4 expression affect CD4+ T cell activation in full length TCR (flTCR) and TCR single chain signaling (TCR-SCS) formats. Here we generated an affinity panel of TCRs from CD4+ T cells and expressed them in flTCR and three TCR-SCS formats modeled after chimeric antigen receptors (CARs) to understand the contributions of TCR-pMHCII affinity, TCR format, and coreceptor CD4 interactions on CD4+ T cell activation. Strikingly, the coreceptor CD4 inhibited intermediate and high affinity TCR-construct activation by Lck-dependent and -independent mechanisms. These inhibition mechanisms had unique affinity thresholds dependent on the TCR format. Intracellular construct formats affected the tetramer staining for each TCR as well as IL-2 production. IL-2 production was promoted by increased TCR-pMHCII affinity and the flTCR format. Thus, CD4+ T cell therapy development should consider TCR affinity, CD4 expression, and construct format.